Asteroseismology of hot B subdwarf stars - Fontaine G.; Brassard P.; Van Grootel V.; Charpinet S.; Green E.M.; Randall S.K. (EPJ Web of Conferences, 2013)
Non-radial pulsations in Extreme Horizontal Branch stars (also known as hot B subdwarfs or sdB stars) offer strong opportunities to study, through asteroseismology, the structure and internal dynamics of stars in this intermediate stage of stellar evolution. Most sdB stars directly descend from former red giants and are expected to evolve straight into white dwarfs after core helium exhaustion. They thus represent the most direct link between these two stages. Their properties should therefore reflect both the outcome of the core evolution of red giant stars and the initial state for a fraction of the white dwarfs. We review the status of this field after a decade of efforts to exploit both p-mode and g-mode pulsating sdB stars as asteroseismic laboratories. From the discoveries of these two classes of pulsators in 1997 and 2003, respectively, up to the current epoch of data gathering of unprecedented quality from space, a lot of progress has been made in this area and prospects for future achievements look very promising.